2021
DOI: 10.2196/26040
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Coping During Venipuncture With Virtual Reality: Pilot Randomized Controlled Trial

Abstract: Background Virtual reality (VR) has shown promise in reducing children’s pain and anxiety during venipuncture, but studies on VR lack objective observations of pediatric coping. Notably, the process of capturing objective behavioral coping data can be labor- and personnel-intensive. Objective The primary aims of this pilot trial were to assess the feasibility of conducting a trial of VR in a pediatric emergency department and the feasibility of document… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…SnowWorld was the first immersive VR game designed for pain reduction in patients undergoing burn wound care (Hoffman et al, 2008). In other studies ( n = 20), children experienced a VR adventure during their medical procedure, such as going on a rollercoaster ride, swimming underwater, travelling around the world or enjoying nature (Althumairi et al, 2021; Aydın & Özyazıcıoğlu, 2019; Canares et al, 2021; Chad et al, 2018; Chan et al, 2019; Chau et al, 2018; Chen et al, 2020; Clerc et al, 2021; Erdogan & Aytekin Ozdemir, 2021; Gerçeker et al, 2020; Gerçeker et al, 2021; Goldman & Behboudi, 2021; Knight et al, 2019; Litwin et al, 2021; Ran et al, 2021; Sander Wint et al, 2002; Scapin et al, 2017; Semerci et al, 2021; Ustuner Top and Kuzlu Ayyıldız, 2021; Xiang et al, 2021). Finally, some children selected a cartoon or movie to watch in their VR headset during their dental or needle‐related procedure ( n = 15) (Ali et al, 2021; Alshatrat et al, 2021; Asl Aminabadi et al, 2012; Felemban et al, 2021; Gerçeker et al, 2018; Koticha et al, 2019; Lee et al, 2021; Mbazzi et al, 2021; Mohanasundari et al, 2021; Niharika et al, 2018; Nunna et al, 2019; Rao et al, 2019; Shetty et al, 2019; Toledo Del Castillo et al, 2019; Wong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SnowWorld was the first immersive VR game designed for pain reduction in patients undergoing burn wound care (Hoffman et al, 2008). In other studies ( n = 20), children experienced a VR adventure during their medical procedure, such as going on a rollercoaster ride, swimming underwater, travelling around the world or enjoying nature (Althumairi et al, 2021; Aydın & Özyazıcıoğlu, 2019; Canares et al, 2021; Chad et al, 2018; Chan et al, 2019; Chau et al, 2018; Chen et al, 2020; Clerc et al, 2021; Erdogan & Aytekin Ozdemir, 2021; Gerçeker et al, 2020; Gerçeker et al, 2021; Goldman & Behboudi, 2021; Knight et al, 2019; Litwin et al, 2021; Ran et al, 2021; Sander Wint et al, 2002; Scapin et al, 2017; Semerci et al, 2021; Ustuner Top and Kuzlu Ayyıldız, 2021; Xiang et al, 2021). Finally, some children selected a cartoon or movie to watch in their VR headset during their dental or needle‐related procedure ( n = 15) (Ali et al, 2021; Alshatrat et al, 2021; Asl Aminabadi et al, 2012; Felemban et al, 2021; Gerçeker et al, 2018; Koticha et al, 2019; Lee et al, 2021; Mbazzi et al, 2021; Mohanasundari et al, 2021; Niharika et al, 2018; Nunna et al, 2019; Rao et al, 2019; Shetty et al, 2019; Toledo Del Castillo et al, 2019; Wong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies found no statistically significant difference between VR distraction and standard of care procedures (Canares et al, 2021; Caruso et al, 2020; Dumoulin et al, 2019; Dunn et al, 2019; G. Gerçeker et al, 2020; Goldman & Behboudi, 2021; Lee et al, 2021; Litwin et al, 2021; Nilsson et al, 2009; Osmanlliu et al, 2021; Sander Wint et al, 2002; Schlechter et al, 2021; Walther‐Larsen et al, 2019). Erdogan and Aytekin Ozdemir (2021) found that children using Buzzy during venipuncture experienced the least pain, followed by VR, distraction cards and standard of care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations